2019
DOI: 10.1111/acel.12933
|View full text |Cite
|
Sign up to set email alerts
|

An early‐senescence state in aged mesenchymal stromal cells contributes to hematopoietic stem and progenitor cell clonogenic impairment through the activation of a pro‐inflammatory program

Abstract: Hematopoietic stem and progenitor cells (HSPC) reside in the bone marrow (BM) niche and serve as a reservoir for mature blood cells throughout life. Aging in the BM is characterized by low‐grade chronic inflammation that could contribute to the reduced functionality of aged HSPC. Mesenchymal stromal cells (MSC) in the BM support HSPC self‐renewal. However, changes in MSC function with age and the crosstalk between MSC and HSPC remain understudied. Here, we conducted an extensive characterization of senescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 55 publications
3
97
0
1
Order By: Relevance
“…As the transplant time lengthened, the serum testosterone level of the iLCs group increased gradually and reached its peak (2.2 ng/mL) 3 weeks after implantation but gradually declined over 3 weeks later. Regarding this phenomenon, there may be many factors involved, such as off‐target effects despite low probability, the senescence of implanted cells caused by adverse factors in vivo, inflammatory reactions and so on, that eventually led to the observed result . The trend of serum testosterone levels after iLCs transplantation was similar to our previous study in vitro .…”
Section: Discussionsupporting
confidence: 82%
“…As the transplant time lengthened, the serum testosterone level of the iLCs group increased gradually and reached its peak (2.2 ng/mL) 3 weeks after implantation but gradually declined over 3 weeks later. Regarding this phenomenon, there may be many factors involved, such as off‐target effects despite low probability, the senescence of implanted cells caused by adverse factors in vivo, inflammatory reactions and so on, that eventually led to the observed result . The trend of serum testosterone levels after iLCs transplantation was similar to our previous study in vitro .…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, Liu et al [118] demonstrated that the loss of osteogenic potential in aged BM-MSCs is mediated by p53 increase through the miR-17 pathway. MSC aging was also correlated to impaired hematopoietic functions: BM-MSCs (fundamental for the maintenance of the hematopoietic stem cell compartment in the bone marrow) from aged donors were shown to activate a SASP-like program contributing to young HSCs functional impairment by promoting an inflammatory state in HSCs [119]. Senescence of synovial and subchondral BM-MSCs is likely to contribute to joint alteration and osteoarthritis (OA) development: this was shown in vitro and in vivo with p16-positive human MSCs co-cultured with OA chondrocytes or intra-articularly injected in young mice [120].…”
Section: In Vivo Msc Senescencementioning
confidence: 99%
“…42 MSCs are known to modulate their tissue micro-environment through their highly diverse secretomic profiles, 43,44 which are drastically altered with age. [45][46][47] As a result, the secretomes from aged bone-marrow derived MSCs have decreased immune-modulatory properties and can impede HSC differentiation and proliferation. 46…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…[45][46][47] As a result, the secretomes from aged bone-marrow derived MSCs have decreased immune-modulatory properties and can impede HSC differentiation and proliferation. 46…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%